Stabilization of Inter-Area Oscillations in a Two-Area Test System via Interval Type-2 Fuzzy Based Dynamic Brake Control (ELEKTRIKA- Journal of Electrical Engineering, 2020)
Inter-area oscillations are, by far, the most detrimental to the synchronous integrity of interconnected power systems. This detriment comes from their wide frequency spectrum and the large numbers of the participant generators. The inherent poor damping associated with the inter-area oscillations leaves open wide probabilities for irrevocable widespread blackouts with the consequent eventual devastating outcomes measured in terms of the huge economic casualties and the possible human fatalities. This article explores the influences of the Interval Type-2 fuzzy logic-based strategized dynamic braking interventions of dual brake models, namely Thyristor Controlled Braking Resistors (TCBRs), for neutralizing the jeopardy of negatively damped inter-area power oscillations in Kundur’s two-area test system, using MATLAB™/Simulink environment. The relative inner generator's speed deviation is employed in this work as a control signal to the proposed controller. The effectiveness of the proposed scheme is authenticated by considering four case studies with different severity degrees. By analyzing the performance repercussions due to four disturbances, without the implementation of the proposed scheme, the unstable nature of the system responses is clearly noticed. With the implementation of the proposed scheme, the system oscillatory behavior is stabilized in an appropriate manner. The performed comparative non-linear time-domain simulation results emphasize the great potential of the proposed scheme in mitigation of inter-area power oscillations according to the considered disturbances. The proposed scheme is simple yet effective in treating the inter-area oscillations appropriately under the considered case studies.
Keywords: Thyristor controlled braking resistor; Fuzzy logic control; Interval Type-2 Fuzzy logic control; Inter-area oscillations; Kundur’s two-area test system.